KARAKTERISTIK TUTURAN HUMOR - Hana Dwi Ratnawati (Belajar Bahasa, 2019)
This study aims to describe the form of violations of the principle of cooperation in the humorous book “Lucu-Lucu Tokoh Dunia” by Isa An. Tamami. The principle of cooperation is a principle that is used as a guideline in communication activities, by applying the four maxims in it, namely the maxim of quantity, the maxim of quality, the maxim of relevance, the maxim of implementation / method. In the conversation humor book “Lucu-Lucu Tokoh Dunia” Figures found elements of violations of the principle of cooperation, so this is what attracts the attention of researchers to make research in pragmatic studies. The method used in this study is descriptive qualitative. The focus of this study lies in the problem of violating the principle of cooperation used in humorous conversations using reading methods and note-taking techniques and certain tips, namely coding and marking each conversation in pencil, with the aim of classifying data according to its maxims. The results of this study indicate that the violation of the principle of cooperation maximizes the quantity used in some humorous book “Lucu-Lucu Tokoh Dunia” conversations is greater than the violation of the principle of cooperation in the maximal implementation / method carried out. Violations of the principle of cooperation can occur because speakers do not understand the context of the conversation, besides that violations are also carried out as a means of creating humor, such as criticizing, insinuating, and entertaining. The researcher found a characteristic form of violation of maxims of quantity, the maxim of quality, the maxim of relevance, the maxim of implementation/method which included: speech characteristics, kibul speech forms, intersection speech forms, ambiguous speech forms. Examinations contained in the humorous book " Lucu-Lucu Tokoh Dunia " often violate the principle of cooperation. That is because to create a funny impression on the utterance.